KEKUATAN MEDIA SEBAGAI AKTOR POLITIK PEMERINTAH DALAM PERUBAHAN SOSIAL MASYARAKAT - Tatik Yuniarti (Avant Garde, 2016)
Media plays an important role as an actor to disseminate information to the public. Without the mass media, the government will be very difficult to reach people quickly. Therefore, the presence of media becomes one of the right channel used as a tool by the government in disseminating information. Through packaging positive content in the media, it is expected to also influence the thoughts and actions of people for social change in achieving development goals